Periprocedural outcomes and early safety with the use of the Pipeline Flex Embolization Device with Shield Technology for unruptured intracranial aneurysms: preliminary results from a prospective clinical study. (20th February 2017) - Martínez-Galdámez, Mario; Lamin, Saleh M; Lagios, Konstantinos G; Liebig, Thomas; Ciceri, Elisa F; Chapot, Rene; Stockx, Luc; Chavda, Swarupsinh; Kabbasch, Christoph; Farago, Giuseppe; Nordmeyer, Hannes; Boulanger, Thierry; et al.
Abstract : Background and purpose: The Pipeline Embolization Device (PED) has become a routine first-line option for treatment of intracranial aneurysms (IAs). We assessed the early safety and technical success of a new version of PED, Pipeline Flex Embolization Device with Shield Technology (Pipeline Shield), which has the same design and configuration but has been modified to include a surface synthetic biocompatible polymer. Materials and methods: The Pipeline Flex Embolization Device with Shield Technology (PFLEX) study is a prospective, single-arm, multicenter study for the treatment of unruptured IAs using Pipeline Shield. The primary study endpoints included the occurrence of major stroke in the territory supplied by the treated artery or neurologic death at 1 year post-procedure. Secondary endpoints included the rate of Pipeline Shield-related or procedure-related serious or non-serious adverse events. Analyses were conducted to evaluate early safety findings in the 30-day post-procedure period as well as technical procedural success outcomes. Results: Fifty patients with 50 unruptured target IAs were enrolled. Mean aneurysm diameter was 8.82±6.15 mm. Thirty-eight aneurysms (76%) were small (<10 mm). Device deployment was technically successful with 98% of devices. Complete wall apposition was achieved immediately post-procedure in 48 cases (96%). No major strokes or neurologic deaths were reported in the 30-day post-procedure period. Conclusions: The results of this first experience with the new Pipeline Flex corroborate the early safety of the device. Mid-term and long-term follow-up examinations will provide data on safety outcomes at the 6-month and 1-year follow-up periods. Clinical trial registration: NCT02390037 .